2014
DOI: 10.3386/w20713
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of Hurricane Katrina on its Victims: Evidence from Individual Tax Returns

Abstract: We thank Jesse Gregory, Bruce Sacerdote, and participants at the 2014 ASSA meetings and 2014 NBER Summer Institute for helpful comments. Erin Robertson and Eric Andersen provided excellent research assistance. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research or the policy of the U.S. Department of Treasury. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
124
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 25 publications
13
124
2
1
Order By: Relevance
“…In other words, were one able to prevent this type of sorting, then the DD estimate using pre-and post-event sales would be larger in magnitude than what it actually recovered, as it would not confound differences in willingnesses to pay across different types of people. Taken together with previous literature's observation of differential patterns of post-disaster migration (e.g., Smith et al 2006;Landry et al 2007;Groen and Polivka 2010;Strobl 2011;Deryugina, Kawano, and Levitt 2014), our results imply that it is thus important to acknowledge the potential for hedonic equilibria to shift in response to disasters and to think about the implications this may have for willingness to pay estimation.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In other words, were one able to prevent this type of sorting, then the DD estimate using pre-and post-event sales would be larger in magnitude than what it actually recovered, as it would not confound differences in willingnesses to pay across different types of people. Taken together with previous literature's observation of differential patterns of post-disaster migration (e.g., Smith et al 2006;Landry et al 2007;Groen and Polivka 2010;Strobl 2011;Deryugina, Kawano, and Levitt 2014), our results imply that it is thus important to acknowledge the potential for hedonic equilibria to shift in response to disasters and to think about the implications this may have for willingness to pay estimation.…”
Section: Resultssupporting
confidence: 83%
“…6 If heterogeneity across individual MWTP exists in the market, the housing price capitalization of the event for nearmiss areas may incorporate both changes to flood risk salience as well as changes in the mix of homebuyers (and their preferences). Existing empirical evidence suggests that this assumption may not hold as some have found heterogeneity in mobility and migration across both race and income following intense disasters (Smith et al 2006, Landry et al 2007, Groen and Polivka 2010, Strobl 2011, Deryugina, Kawano, and Levitt 2014.…”
mentioning
confidence: 99%
“…Our paper is most similar to Deryugina et al [2014] who, using tax return data, find a fairly modest effect on personal finances for those individuals living in New Orleans at the time of flooding. Deryugina et al [2014] ask what the total effect of Katrina is on individual outcomes for residents of New Orleans as compared with a control group outside the city. Our estimates, by construction, net out any common shock to New Orleans.…”
Section: Introductionsupporting
confidence: 71%
“…2 Katrina is easily the most costly hurricane in terms of property damage in US history. Nevertheless, despite the massive economic damage, little is known about the financial impact of Katrina on individual residents (Deryugina et al [2014]; Gregory [2013]).…”
Section: Hurricane Katrinamentioning
confidence: 99%
“…In their study, businesses that suffered the greatest economic impact closed operations immediately following Katrina. While Deryugina et al (2014) found that federal aid and TORRES ET AL. | 169 recovery programmes were sufficient to cover the economic impact in New Orleans in just a few years, Josephson and Marshall (2016) reported a lack of success in the targeted Small Business Administration (SBA) disaster loans to female-owned and coastal small businesses.…”
Section: Hurricane Katrinamentioning
confidence: 99%